2017
DOI: 10.1016/j.ijheatmasstransfer.2017.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Numerical quantification of coupling effects for radiation-conduction heat transfer in participating macroporous media: Investigation of a model geometry

Abstract: a b s t r a c tRadiative-conductive heat transfer in porous media is usually investigated by decoupling the heat transfer modes and solving the volume-averaged continuum equations using effective transport properties. However, both modes are naturally coupled and coupling effects might significantly affect the results. We aim at providing quantitative understanding of the coupling effects occurring in a model geometry. This is an important first step towards improving the accuracy of heat transfer predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…This formula entirely coincides with Formulas (4) and (5). In addition, we found that the radiant thermal conductivity approximation is valid with the condition (22) and with the accuracy (26).…”
Section: Radiant Thermal Conductivity Of a Grey Mediumsupporting
confidence: 79%
See 1 more Smart Citation
“…This formula entirely coincides with Formulas (4) and (5). In addition, we found that the radiant thermal conductivity approximation is valid with the condition (22) and with the accuracy (26).…”
Section: Radiant Thermal Conductivity Of a Grey Mediumsupporting
confidence: 79%
“…Most of the problems of radiative-conductive heat transfer in a medium are solved based on "the radiation transfer equation" [4][5][6][7][8][9]. Recall that the law of conservation of energy is not enough to solve such problems.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of high-temperature physics implicates accurate prediction of heat transport as one of the primary factors for optimizing the global performance of these systems. As such, many researchers have focused on studying (numerically or experimentally) the behavior of open-cell cellular ceramics at high temperatures, especially at temperatures beyond 1200 K [7,8,9,10]. Complementary to these researches, the current article focuses on analyzing coupled conductive-radiative heat transport of topologically different open-cell cellular ceramics up to 1800 K.…”
Section: Introductionmentioning
confidence: 99%
“…However, when conjugate heat transfers are being investigated, the present-day numerical approaches are limited to 3D images with modest volumes. This is due to important computational cost required to reproduce the underlying heat transfers [18,10]. Detailing and solving accurately discrete problems on these complex geometries requires meshes with large number of elements.…”
Section: Introductionmentioning
confidence: 99%
“…Such a discrete-scale approach, finely described in a previous work [19], makes it possible to achieve a good level of details in terms of three-dimensional temperature fields, conductive flux fields, and radiative flux fields. This is important because, at high temperature, heat transfer modes are coupled in such a way that a given heat transfer mode is affected by the other modes, making their effective contribution non linear [20].…”
Section: Introductionmentioning
confidence: 99%